PRESERVING WOET IE BU PEUDAH TRADITION AS A CULTURAL HERITAGE: A CASE STUDY IN GAMPONG LIMPOK, DARUSSALAM DISTRICT, ACEH BESAR REGENCY - Fira Fahrika; Sanusi Ismail; Bustami Abubakar (Indonesian Journal of Islamic History and Culture, 2021)
This study aims to examine the making process, social meaning, and function of Ie Bu Peudah and its conservations. The method used in this study is a qualitative method in which the researcher himself is the key instrument. Data collection techniques is conducted through observation, interviews, and documentation. The results obtained from this study concludes that the Woet Ie Bu Peudah tradition has existed since the days of the Aceh Darussalam sultanate and still survives to the present day. The process of making this traditional food is complex, starting from collecting and drying the ingredients to being ground to mash. Meanwhile, Ie Bu Peuda's cooking process takes approximately two hours. The meaning of this tradition among the people of Gampong Limpok, among others, is as a liaison for friendship and also serves as the main menu for breaking the fast. While the efforts made to preserve it include the Gampong Limpok administrations allocating particular funds for this tradition that comes from the APBG, but several things that become obstacles to the continuity of this tradition include, the ingredients for making it that are starting to be difficult to find and its presence only at special moments. certain only